The Dialectic of Life in Hegel’s Thought. An Introduction - Battistoni, Giulia (ETHICS IN PROGRESS, 2025)
This issue of Ethics in Progress titled Unfolding Life – The Dialectic of the Living in Hegel’s Thought. Philosophical Foundations and Contemporary Resonances builds upon the discussions initiated in issue no. 2/2024 of the journal, which explored the enduring relevance of Hegel’s early philosophy through the theme Nature and Spirit. While continuing along that trajectory into Hegel’s mature philosophy, the present issue narrows its focus to a central dimension of Hegel’s Philosophy of Nature: the concept of life in its diverse manifestations. The contributions investigate various forms of living being – plant, animal, and human – examining their underlying impulses, structural dynamics, and vulnerabilities. Together, the essays highlight how Hegelian philosophy offers critical resources for engaging with contemporary questions about the nature and conditions of life.